Manajemen Risiko Penyakit Unggas pada Peternak dan Pedagang Ayam Broiler di Jawa Barat - Ismail, Muhammad; Cahyadi, Eko Ruddy; Hardjomidjojo, Hartrisari (Institut Pertanian Bogor, 2019)
Livestock products are an important commodity in Indonesia. Broiler chickens are one of the main consumption commodities in the community. The high demand for broiler chickens needs to be accompanied by supervision of product quality. Product quality control is one of them is the management of poultry disease risk. The research objective is to determine the behavior of breeders and traders in mitigating the spread of poultry disease. This study was conducted by mapping the supply chain of live broiler chickens to find out the distribution channel, analyzing the behavior of breeders and traders to determine optimal disease mitigation, and multiple linear regression analysis to determine the causes of death. Research locations were conducted in four regions, namely Ciamis Regency, Tasikmalaya Regency, Subang Regency, and Sukabumi Regency. The results of the study show that the supply chain of broiler chickens is different for each region. The longer the distribution channel, the higher the risk of spreading the disease. breeders and traders generally know poultry diseases and the symptoms of chickens infected with the disease. Knowledge of breeders and traders about bird flu symptoms that are better proven to reduce the risk of death of broiler chickens during handling. More than 64% breeders chose to separate sick chickens form healthy chickens, 22% chose to treat sick chikens, 11%sold all si hicens, and 3% destroyed sick chikens. The majority of traders mitigate the disease only by cleaning vehicles and baskets without disinfectants. The mortality rate of chickens in traders significantly increased along with the increase in the number of purchases and the distance of transportation.